Reducing Plagiarism of Undergraduate Students' Thesis Proposal by Using QuillBot Paraphraser - Sri Wahyuni; Syarifuddin Dollah; Fatimah Hidayahni Amin (International Journal of Language, Education, and Literature, 2025)
The intention of this study is to determine how students experience about using QuillBot as a tool to minimise plagiarism in their thesis proposals. To accomplish the objectives of the study, a quantitative research approach was used. Data were collected through a structured questionnaire distributed to seventh-semester undergraduate students majoring in English Education at STKIP YPUP Makassar during the 2023/2024 academic year. According to the results, 60% of students think QuillBot is helpful for paraphrasing, and 40% concur that it is user-friendly and beneficial. Additionally, all participants (100%) agreed that QuillBot is a useful tool for paraphrasing. After using QuillBot, most students reported improvements in their writing clarity (60%) as well as in their grammar and sentence structure. Furthermore, 40% of students strongly suggested QuillBot to others, and 60% of students said they would be willing to keep using it. These findings imply that QuillBot is an effective supporting tool for encouraging academic integrity and helping students develop their academic writing, even though some students still need more direction to make the most of it.